Pengolahan Kopi Bubuk dan Pemasaran Berbasis Digital Marketing dalam Meningkatkan Daya Saing Hilirisasi Kopi di Kawasan Lereng Menoreh - Ahmad, Masrukan; Perdana, Fahmi Rafika; Utami, Kristiana Sri; Harjanta, Sri Lestari (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
Diversification of post-havesting of coffe managed by the coffee farming group in the Sidoharjo district, Kulonprogo has several problems in post-harvest handling and processing coffee, especially in processing of coffee powder Â with good manufacturing process (gmp) as well as conventional marketing management. Through the Community Partnership Program (PKM), the service team provide solutions to outcome problems through several methods; 1) training and assistance in post-harvest handling Â 2) training and assistance in the production of ground coffee in a natural process and 3) training and assistance in marketing management with digital marketing. The results of the assistance are the post-harvest handling and processing of coffee properly and correctly by producing ground coffee with the brand name